Analisa Perbandingan Volume dan Biaya Bar Bending Schedule dengan Metode SNI-2847:2013 dan BS 8666:2005 (Studi Kasus: Proyek Pembangunan Kantor Pacto, Denpasar-Bali) - Made Widya Jayantari; Putu Surya Triana Dewi; Putu Gede Anggara Yoga (Universitas Pendidikan Nasional, 2022)
The success of construction projects, especially in the construction of multi-storey buildings is influenced by material components. Therefore, optimizing material planning is important to do. In the Pacto Sanur Building construction project, optimization of material planning is viewed from the ironing work because it costs a relatively large amount compared to other works. The purpose of this study is to analyze the comparison of bar bending schedules on projects using the British Standard 8666:2005 and SNI-2847:2013 methods, then to identify project cost comparisons. From the results of the identification of iron planning using the SNI-2847:2013 method, it can be seen that the weight of Ø16 iron = 3971.00 kg, the weight of Ø13 iron = 251.51 kg, and the weight of Ø10 iron = 7034.38 kg. Furthermore, in the identification of repair plans using the British Standard 8666:2005 method, it can be seen that the weight of iron Ø16 = 42153.22 kg, the weight of iron Ø13 = 280.95 kg, and the weight of iron Ø10 = 7343.58 kg. The volume optimization for Sloof, Beams, Columns, and Floor Plates II uses the British Standard 8666: 2005 method of 47% with the total cost of the SNI-2847:2013 method ironwork Rp. 202,623,928 and the total cost of repair work using the British Standard 8666:2005 method is Rp. 213,799,435.